2004
DOI: 10.1128/jcm.42.1.119-125.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Mycobacterium kansasii Isolates from the United States

Abstract: We studied the population genetics of Mycobacterium kansasii isolates from the United States by PCR restriction enzyme analysis (PRA) of the 441-bp Telenti fragment of the hsp-65 gene and pulsed-field gel electrophoresis (PFGE) of genomic DNA with the restriction endonucleases AseI, DraI, and XbaI, and we compared the patterns to those previously reported from France and Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…The three genetic types were also the only ones detected among the 163 clinical isolates studied by Alcaide et al (1997), 111 (68%) of them were characterized as type I, 50 (31%) type II, and only 2 (1%) as type III. Of the 113 isolates obtained from the Alcaide et al (1997), Picardeau et al (1997), and Zhang et al (2004), as in the present study, indicate that this type of strain may present an association of virulence confering upon it a greater capacity for colonization and/or pathogenic activity for human beings, while the data available for the strains of genetic type II suggest that is a type less able to overcome natural resistance mechanisms and behaving in a more opportunistic manner.…”
Section: Discussionmentioning
confidence: 98%
“…The three genetic types were also the only ones detected among the 163 clinical isolates studied by Alcaide et al (1997), 111 (68%) of them were characterized as type I, 50 (31%) type II, and only 2 (1%) as type III. Of the 113 isolates obtained from the Alcaide et al (1997), Picardeau et al (1997), and Zhang et al (2004), as in the present study, indicate that this type of strain may present an association of virulence confering upon it a greater capacity for colonization and/or pathogenic activity for human beings, while the data available for the strains of genetic type II suggest that is a type less able to overcome natural resistance mechanisms and behaving in a more opportunistic manner.…”
Section: Discussionmentioning
confidence: 98%
“…However, with the CM/AS assay, the most common clinical isolates of these groups were identified. For instance, M. kansasii sequevar I represents the most common clinical isolate from humans (1,25) and also in our laboratory the majority of the clinical strains identified belong to M. kansasii sequevar I. M. kansasii sequevars III, IV, and V have been isolated much less commonly from humans but have been found in environmental samples (1,12,32). Concerning M. intracellulare subspecies, frequencies of isolated strains differ markedly and M. intracellulare serovar 7 belongs to the rarer isolates found in human specimens (18).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular strain typing analyses have demonstrated that M. kansasii consists of a heterogeneous group including several distinct subtypes (Alcaide et al, 1997a;Picardeau et al, 1997;Ross et al, 1992;Zhang et al, 2004). Worldwide, M. kansasii genotype I, as defined by PRA, appears to be highly clonal and is the most common genotype associated with human disease (Zhang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%